1998
DOI: 10.1177/001440299806400201
|View full text |Cite
|
Sign up to set email alerts
|

Initiating and Fading Self-Management Interventions to Increase Math Fluency in General Education Classes

Abstract: This study investigated the effects of multiple-component behavioral self-management (BSM) interventions on math fluency and engaged time of five 4th-grade students with and without disabilities in general education classrooms. A multiple-baseline across subjects design demonstrated that the students (a) increased their math fluency and engaged time after being trained to use self-management components, (b) further improved their math fluency and engaged time when components of the self-management intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
31
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 45 publications
4
31
1
1
Order By: Relevance
“…In terms of academic engagement when the ACT-REACT strategic self-monitoring sheet was gradually faded, the results of this study support those obtained in the ten previous self-monitoring investigations that included fading in their experimental phases (see Boyle and Hughes 1994;De Haas-Warner 1992;DiGangi et al 1991;Edwards et al 1995;Levendoski and Cartledge 2000;Mathes and Bender 1997;Maag et al 1993;McDougall and Brady 1998;Prater et al 1991Prater et al , 1992. In this study, all of the students demonstrated markedly improved levels of academically engaged behavior during fading when data are compared to baseline phases.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In terms of academic engagement when the ACT-REACT strategic self-monitoring sheet was gradually faded, the results of this study support those obtained in the ten previous self-monitoring investigations that included fading in their experimental phases (see Boyle and Hughes 1994;De Haas-Warner 1992;DiGangi et al 1991;Edwards et al 1995;Levendoski and Cartledge 2000;Mathes and Bender 1997;Maag et al 1993;McDougall and Brady 1998;Prater et al 1991Prater et al , 1992. In this study, all of the students demonstrated markedly improved levels of academically engaged behavior during fading when data are compared to baseline phases.…”
Section: Discussionsupporting
confidence: 87%
“…As we mentioned previously, we found only five studies (see DiGangi et al 1991;Edwards et al 1995;Levendoski and Cartledge 2000;Maag et al 1993;McDougall and Brady 1998) in which researchers investigated students' academic performance during fading conditions and results were also mixed.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Therefore, becoming fluent in arithmetic operations in math will have positive effects on academic performance, home tasks, shopping and other areas of daily life. But without interventions, learning disabilities in math persist into adulthood (Chiesa & Robertson, 2000;McDougall & Brady, 1998;Woodward, 2006). Thus, educators should use effective and encouraging teaching strategies about math while working with students with visual impairments.…”
Section: Extended Abstractmentioning
confidence: 99%